Energy Transition in Northern Netherlands: seeking a balance between top-down and bottom-up initiatives - Oldenbroek, Bas; Psarra, Ifigenia; van der Schoor, Tineke; Tjahja, Cyril (Open research Europe, 2024)
This study focuses on top-down and bottom-up processes within the field of energy transition. It aims at gaining insights into the ways that a more balanced approach can be achieved, by taking into consideration the (mutual) interests, barriers and expectations of the municipality and local citizen initiatives. The theoretical framework of the study is the implementation analysis framework, distinguishing top-down and bottom-up approaches. Specifically, this qualitative (thematic analysis) research study investigates the mismatch in expectations between a number of local energy initiatives and the municipality of Groningen regarding their roles within the local energy transition context. To this end, semi-structured interviews have been conducted with members of the municipality of Groningen, Grunneger Power (a local energy intermediary), and four local energy initiatives. Need and expectation gaps have been identified and potential solutions have been explored. The main findings of the study illustrate the need of professional support for citizen initiatives, at both technical and organizational level, especially in the first phases of their development. Additionally, clear mutual communication on short and long-term planning and ambitions of the involved parties is of key importance for the alignment of the interests and the course of actions. Consequently, a clear context is needed, within which an exchange of feedback on the envisioned strategies, and the subsequent energy saving or generation interventions, can take place in an efficient and effective way. Additionally, such a context increases confidence and provides a clear understanding to the citizen initiatives regarding their role and the level and nature of support they can expect in their intended projects and activities. Based on these findings, policy implications have been drawn.